Pattern of Lipid Profile in Patients with Cholelithiasis (Journal of Dhaka National Medical College & Hospital, 2016)
Background: Cholelithiasis is one of the most common surgical problem and gastrointestinal diseases throughout the world but its pathogenesis remains unclear. Lipid in the blood play a key role in the aetiology of cholelithiasis. Especially in cholesterol gallstones formation blood lipids are altered which is suggestive of metabolic syndrome. Multiple studies have shown that there is an association between gallstones and abnormal lipids. There is no previous study to explore the pattern of lipid profile in patients with cholelithiasis in Bangladesh. The aim of this study was to evaluate the pattern of lipid profile in patients with cholelithiasis.Methods: This cross sectional study was carried out on patients based on clinical and imaging features confirming symptomatic cholelithiasis patients. In this study 100 confirmed patients of cholelithiasis aged 30 to 70 years of both male & female were included as cases & 100 age & sex matched healthy subjects were included as controls. Serum total cholesterol, HDL-cholesterol & serum triglycerides level were estimated by enzymatic method. Serum LDL-cholesterol was calculated by Fried walds formula. The groups were compared by using Student's t-test, p